ENGLISH LANGUAGE TEACHING AND LEARNING: THEORY AND PRACTICE – A PLPG MODULE - Linda Ivonne Rupidara (Academic Journal of Educational Sciences, 2019)
In this article, the writer argues that the module entitled English Language Teaching and Learning: Theory and Practice written by Endang Fauziati et al. (published digitally in 2011, 297 pages) has both strengths and weaknesses. Its strengths are related to the theories of education which are comprehensively presented in the module, its clear flows of thinking, and some great evaluations at the end of each chapter. Its weaknesses are related to such issues as its content, approach, and objectives. It is concluded that despite those weaknesses, the module is generally great and it is, therefore, important for the improvement of teaching and learning in general, in English in particular.